2002
DOI: 10.1105/tpc.002998
|View full text |Cite
|
Sign up to set email alerts
|

Signal-Mediated Depolymerization of Actin in Pollen during the Self-Incompatibility Response

Abstract: Signal perception and the integration of signals into networks that effect cellular changes is essential for all cells. The self-incompatibility (SI) response in field poppy pollen triggers a Ca 2 ؉ -dependent signaling cascade that results in the inhibition of incompatible pollen. SI also stimulates dramatic alterations in the actin cytoskeleton. By measuring the amount of filamentous (F-) actin in pollen before and during the SI response, we demonstrate that SI stimulates a rapid and large reduction in F-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
225
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(253 citation statements)
references
References 77 publications
26
225
2
Order By: Relevance
“…Because SI stimulated rapid actin depolymerization (Snowman et al, 2002), we wondered whether this might be responsible for alterations to the microtubules. We used latrunculin B (LatB) to examine the effect of F-actin depolymerization on the pollen microtubule cytoskeleton.…”
Section: Actin Depolymerization Results In Alterations To the Microtumentioning
confidence: 99%
See 3 more Smart Citations
“…Because SI stimulated rapid actin depolymerization (Snowman et al, 2002), we wondered whether this might be responsible for alterations to the microtubules. We used latrunculin B (LatB) to examine the effect of F-actin depolymerization on the pollen microtubule cytoskeleton.…”
Section: Actin Depolymerization Results In Alterations To the Microtumentioning
confidence: 99%
“…We have shown that SI triggers both actin depolymerization (Snowman et al, 2002) and apparent microtubule depolymerization. Moreover, depolymerizing actin with LatB triggers microtubule depolymerization, while depolymerizing microtubules with oryzalin has no effect on actin organization, as also previously shown by Gossot and Geitmann (2007).…”
Section: Evidence For Cross Talk Between Actin and Tubulinmentioning
confidence: 99%
See 2 more Smart Citations
“…23.1a,b . Depolymerization of the actin fi lament bundles occurs within a few minutes of SI induction (Snowman et al 2002 ), which provides a highly effective mechanism to rapidly inhibit incompatible pollen tube growth. Two Ca 2+ -dependent actin-binding proteins (ABPs) that could potentially act synergistically in SI-induced depolymerization are profi lin and PrABP80 (a putative gelsolin), which has potent Ca 2+ -dependent severing activity ).…”
Section: Si-induced Alterations To F-actinmentioning
confidence: 99%